Biocidal radiuses of cycloxaprid, imidacloprid and lambda‐cyhalothrin droplets controlling against cotton aphid (Aphis gossypii) using an unmanned aerial vehicle. Issue 9 (25th May 2020) - Nahiyoon, Shahzad Ali; Cui, Li; Yang, Daibin; Yan, Xiaojing; Rui, Changhui; Yuan, Huizhu
Abstract: BACKGROUND: Unmanned aerial vehicles (UAVs) are a recently advanced aerial spraying technology. However, the median lethal number of droplets (LN50 ) and biocidal radiuses ( r 50 ) of insecticides droplets sprayed by UAVs are still unknown. Therefore, we evaluated the LN50 and r 50 of cycloxaprid, imidacloprid and lambda‐cyhalothrin droplets associated with adjuvant controlling against Aphis gossypii . RESULTS: A small UAV and Potter spray tower (PST) were used to generate different size of droplets (Dv0.5 = 185 ± 5 and 43 ± 2 μm). The mortality of A. gossypii showed a droplet density‐dependent process. At the concentration of 5 g L −1, the LN50 of lambda‐cyhalothrin, imidacloprid and cycloxaprid droplets sprayed by the UAV were only 49.2, 34.6 and 19.7 droplets cm −2, respectively, and the r 50 were 0.57, 0.68 and 0.90 mm, respectively. The LN50 values were negatively correlated with insecticide concentrations, but the r 50 values increased with the increasing concentrations. Although cycloxaprid is less toxic to A. gossypii than lambda‐cyhalothrin, cycloxaprid had a larger r 50 than lambda‐cyhalothrin due to its translocation ability. Furthermore, cycloxaprid had a relatively larger r 50 than imidacloprid because it is more toxic to A. gossypii . Moreover, adjuvant silwet DRS‐60 can significantly increase the r 50 of droplets. CONCLUSION: Our results revealed that the r 50 of a droplet was higher than its droplet size at tested concentrations. Smaller droplets generated by the PST had relatively higher insecticidal potential. The median lethal dose (LD50 ) and translocation ability of insecticides and spray adjuvant contributed to their r 50 . Therefore, ultra‐low‐volume spray with UAVs is feasible to control cotton aphids. © 2020 Society of Chemical Industry Abstract : There is a need for estimating the biocidal potential of droplets. This article presents the biocidal radiuses of cycloxaprid, imidacloprid and lambda‐cyhalothrin droplets sprayed by unmanned aerial vehicles.